2022
DOI: 10.3390/ijerph19137631
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Psychological Impacts of COVID-19 Social Restrictions on International University Students: A Qualitative Study

Abstract: The global COVID-19 pandemic has impacted on the mental well-being of university students, but little attention has been given to international students, who may have a unique experience and perspective. The aim of this study was to explore the views of international students and university staff towards COVID-19 restrictions, self-isolation, their well-being, and support needs, through eight online focus groups with international students (n = 29) and semi-structured interviews with university staff (n = 17) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 49 publications
(71 reference statements)
1
21
0
Order By: Relevance
“…An Australian study found students used video chats, social media, took up exercising and engaged in new hobbies to cope with the pandemic [ 28 ]. Similar findings have also been presented from a qualitative study conducted among international students registered in an UK university where students shared about watching movies, chatting with friends and family and exercising as coping strategies they employed during the pandemic [ 33 ]. Alongside positive coping, some studies also found students engaging in negative coping strategies such as smoking and alcohol consumption to get through the pandemic [ 9 , 26 , 34 ].…”
Section: Introductionsupporting
confidence: 75%
“…An Australian study found students used video chats, social media, took up exercising and engaged in new hobbies to cope with the pandemic [ 28 ]. Similar findings have also been presented from a qualitative study conducted among international students registered in an UK university where students shared about watching movies, chatting with friends and family and exercising as coping strategies they employed during the pandemic [ 33 ]. Alongside positive coping, some studies also found students engaging in negative coping strategies such as smoking and alcohol consumption to get through the pandemic [ 9 , 26 , 34 ].…”
Section: Introductionsupporting
confidence: 75%
“…However, since the beginning of the COVID-19 pandemic, university students had to also deal with further changes which abruptly occurred in their life [ 8 , 9 ], potentially eliciting notable levels of stress related to the control measures (i.e., isolation due to the lockdown) and to the fear of being infected and infecting others, as well as to the drastic modifications in the relational and social life [ 10 , 11 , 12 ]. From this perspective, the COVID-19-related changes have deeply affected students’ interpersonal life, entailing specific experiences (i.e., loneliness; lack of connection; a frustrated sense of belonging) which expose them to a significantly high risk for psychological health [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…ATS staff proposed that some students did not engage in testing to avoid the possibility of self-isolation. Self-isolation has been particularly challenging for university students, as evidenced by studies exploring the practical, social, and psychological impacts of social restrictions in student samples at the same institution, across various stages of the pandemic [ 2 , 3 , 60 ]. Regarding testing uptake, it has previously been advocated that uptake, adherence and satisfaction with testing is likely to be influenced by the level of support provided to students who are self-isolating [ 28 , 61 ].…”
Section: Discussionmentioning
confidence: 99%